The US Sub-Prime Mortgage Crisis - Causes and Implications - Balaji, C. D. (Indian Journal of Finance, 2009)
The US sub-prime mortgage crisis has turned out to be a full-blown global financial crisis with experts terming it as a financial tsunami. Countries in the world have been witness to and suffered from the impact of the bursting of several such bubbles in the past such as the tulip bubble mania in 1630's, the South Sea Bubble and the Mississippi Bubble in the 18th Century, Florida's real estate bubble ion 1920's, the stock market crash in 1929 and 1987 etc.,. The difference between the crisis witnessed in the past and the present one is that in the past, the negative impact would be felt in a particular country or in a few of its neighbors, but with the globalization of financial markets, the financial crisis in the US has engulfed the entire world, the only difference being the level of its impact on various countries. Apart from the magnitude of the problem (losses due to the sub prime crisis are expected to be upwards of $2 trillion), what really complicates it is the fact that to this date, the actual extent of losses cannot be gauged. For instance in July 2007, the Federal Reserve Chairman, Bernanke had said that sub prime losses would be less than $100 billion but by August 2008 nearly $500 billion of losses due to the crisis had been written off. The sub-prime mortgage crisis happened because the financial institutions in the US sacrificed morals and prudence at the altar of greed. Weak regulation, market fundamentalism and innovation with wrong intentions are the main reasons for the financial inferno. Galbraith, the famous economist had pointed out the cause for such bubbles several decades ago in his statement, "seemingly imaginative, currently lucrative and eventually disastrous innovation in financial structures. The banks needless to say provided the money that financed the speculation that in each case preceded the crash." The crisis is a pointer to the fact that the world has not learnt its lessons from the past.